Model bisnis pada usaha UMKM Aqueena sambal ikan gabus Kota Samarinda dengan pendekatan buisness model canvas - Zulkipli; Erwiantono; Darmansyah, Oon (Universitas Halu Oleo, 2024)
This research was conducted with the aim to know business canvas model is currently used in the Aqueena snakehead fish sauce MSMEs business and whether this business is feasible. This research was conducted for 12 months, from June 2022 to June 2023. MSMEs fish sauce processing located at Samarinda, Samarinda Ulu District, Air Hitam sub-district. The method that being used in sampling the processing of MSMEs snakehead fish sauce is purposive method where the selected MSMEs is Aqueena snakehead fish sauce, and the analysis method uses descriptive qualitative and quantitative. The business model canvas showed that adult customers aged 20-60 years, instagram users, Banjar people and who are fans of processed chili products, the value of this proposition is having a PIRT and Halal permit certificate, using onions. Dayak, and using aluminum foil lid packaging, offline media channels product exhibitions and online media Instagram, customer relations direct suggestions and criticism from customers, key resources physical resources, financial resources, human resources and intellectual resources, key activities production activities, sales, partnerships and product development, key partnerships for suppliers of raw materials for the Selili and Segiri markets in Samarinda City, Bank Indonesia Kalimantan Timur and the Samarinda MSMEs trade service. Based on the results of business analysis calculations, investment costs are IDR 5,159,835 fixed costs IDR 92,421 variable costs IDR 4,481,690 total costs IDR 4,574.11 per month. RCR of 2.5 BEP price IDR. 11,435 BEP production 152.4 bottles BEP sales IDR.151,509 Payback Period 0.69 months or 20.7 days Return on Investment 143.9%.